Aplikasi Teknik Behavior Activation untuk Meningkatkan Perilaku Tanggung Jawab dalam Paternal Involvement pada Ayah di Jabodetabek - Asyari*, Hasyim; Ariyanto, Amarina (Universitas Syiah Kuala, 2023)
This study aims to make intervention model to improve behavior of responsibility in paternal involvement. The method used in this research is qualitative and quantitative approach with sample size of 23 respondents. The criterion of respondents are fathers, having children age 2-12 years old, and lives in Jabodetabek. The design of intervention program used quasi experimental one group pre-test and post-test methods with behavioral change techniques through training and application of behavioral activation technique. Statistical analysis of mean comparisons using wilcoxon signed-ranks non parametric test having average of responsibility behavior in paternal involvement in the post-test (M = 32.65; SD = 1,027) is higher than pre-test (M = 25; SD = 4.758). Meanwhile the post-test score of responsibility behavior in paternal involvement has significantly higher score than pre-test score (Z = -4.203), with value (Asymp. Sig 2 tailed) is 0,000, with 0.05 l.o.s. These results are same with analysis of the qualitative study showed that responsibility behavior in paternal involvement after training and application of behavioral activation techniques have increased. Such outcome proved that intervention model succeeded to improve behavior of responsibility in paternal involvement of fathers in Jabodetabek.